Ecological Study of Vanellus indicus in District Narowal, Pakistan - Ahmad, Waqar; Qureshi, Asif Mehmood; Javed, Anam (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Red wattled lapwing is commonly found and endemic species of Asian agricultural lands. Its preferred habitat is airy lands, rural and even urban areas. The main aims of current investigatory effort were the observation of different parameters of breeding ecology of Vanellus indicus including breeding sites, incubation period, the clutch size, survival rate of chicks and possible reasons of their mortality which are localized in Narowal district. Red wattled lapwings forage on several types of insects, snails, seeds, and of invertebrates. Experimental observations highlight that the annual breeding season is of average 26-30 days of V. Indicus begins from the March and till the end of August. Moreover, the weight of their eggs falls between 22.0 to 28.0g. These findings about local species may serve for next experimental designs based of on V. indicus and further focus should be on those factors which may improve its breeding. Similarly, the estimation of feeding preferences of this species can directly help in low cost biological control management for crops.